Assessment of Knowledge regarding Vitamin D among Medical Undergraduate Students - Manandhar, Pratibha; Manandhar, Naresh; Joshi, Sunil Kumar (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: It is estimated that one billion people in the world have vitamin D deficiency and observed as a public health problem. The main objective of this study is to assess and compare the Vitamin D knowledge among MBBS, BDS and BSc. Nursing students of Kathmandu Medical College, Duwakot (before and after educational training). Methods: This is a cross sectional study carried out at Kathmandu Medical College, Duwakot among 1st year MBBS, BDS and B.Sc Nursing students. Data was collected from 2nd -15th February 2020. A structured self designed multiple choice questionnaire was used. A written pretest assessment regarding vitamin D knowledge followed by a written posttest assessment was taken after a lecture class on vitamin D. Ethical approval was obtained from Institutional Review Committee of Kathmandu Medical College (Ref. 2812201809). The census data of students were taken. The data was analyzed using SPSS software version 20.0 Results: Mean differences between the pretest and posttest scores showed an increment of vitamin D knowledge among MBBS students (t = 22.155, p = 0.000), BDS students (t = 16.46, p = 0.000) and B.Sc. Nursing students (t = 18.615, p = 0.000). Conclusions: Interactive lecture class showed moderate gain on knowledge regarding vitamin D among the under graduate students. Health education interventions can improve the knowledge and increases self-efficacy of future doctors and nurses about vitamin D.